Regimes for the execution of sentences and rights and obligations of sentenced persons - Anane, Iuliana (Technium Social Sciences Journal, 2023)
Correcting deviant behavior has been a problem for society since ancient times. In order to find out what is the most appropriate way to proceed with the retouching of deviant behavior, we must know about the cause of the criminal urge, look for the psychological springs that impel an individual to resort to committing violations of the criminal law. A determining factor is also played by the significant discrepancy between social categories through the unequal distribution of income, which also influences the quality of living standards, living and purchasing power. In this respect, it was desired to join the OECD, being perceived as a means of activating national reforms that have as main objective the improvement of the material situation of citizens. The Organization for Economic Co-operation and Development is an international body that aims to ensure sustainable economic growth and social stability of 35 developed countries that accept the principles of democracy and free market economy. With Romania’s accession to the European Union, it was also desired to get closer to the other European states in order to borrow the methods and measures applied that contribute to maintaining a state of general stability. However, integration did not occur with accession, as demonstrated by repeated refusals and barriers to acceptance into various European and international organizations, the most famous case being the desire to enter the Schengen area, a wish rejected, even if the accession criteria are met. Due to such a vast history with reference to the penitentiary setting, but also due to the worldly character attributed to the execution of custodial measures in recent years, we will go through together the evolution of the penitentiary regime and of the rights and obligations of convicted persons, so that in the end we will see if all these measures to correct those who conduct themselves deviate from the rules admitted by society lead to the expected result.